The Methylation Game: Epigenetic and Epitranscriptomic Dynamics of 5-Methylcytosine - Alagia, Adele; Gullerova, Monika (Frontiers in Cell and Developmental Biology, 2022)
DNA and RNA methylation dynamics have been linked to a variety of cellular processes such as development, differentiation, and the maintenance of genome integrity. The correct deposition and removal of methylated cytosine and its oxidized analogues is pivotal for cellular homeostasis, rapid responses to exogenous stimuli, and regulated gene expression. Uncoordinated expression of DNA/RNA methyltransferases and demethylase enzymes has been linked to genome instability and consequently to cancer progression. Furthermore, accumulating evidence indicates that post-transcriptional DNA/RNA modifications are important features in DNA/RNA function, regulating the timely recruitment of modification-specific reader proteins. Understanding the biological processes that lead to tumorigenesis or somatic reprogramming has attracted a lot of attention from the scientific community. This work has revealed extensive crosstalk between epigenetic and epitranscriptomic pathways, adding a new layer of complexity to our understanding of cellular programming and responses to environmental cues. One of the key modifications, m5C, has been identified as a contributor to regulation of the DNA damage response (DDR). However, the various mechanisms of dynamic m5C deposition and removal, and the role m5C plays within the cell, remains to be fully understood.